Penerapan Kurikulum Merdeka Sebagai Upaya Dalam Mengatasi Krisis Pembelajaran (Learning Loss) Pada Mata Pelajaran Pendidikan Agama Islam Kelas X Di SMA Negeri 12 Bandar Lampung - Margiyono Suyitno; Trisna Rukhmana; Ai Siti Nurmiati; Fajar Romadhon; Irawan Irawan; Sabil Mokodenseho (Departement of Mathematics Education, 2023)
Research has been carried out on the application of Independet Curriculum as an effort to overcome the Learning Loss in Islamic Education subject at SMAN 12 Bandar Lampung. This research was conducted to provide good information to educational units, students as well as parents and even education stakeholders regarding a clear description of the characteristics offered by the independent curriculum which has comparisons with K-13 so as to provide solutions for the world of education to overcome the learning crisis that occurs at the moment. This study uses research methods with the type of field research (field research) and the nature of descriptive qualitative research. The data collection method is through observation, interviews, and documentation. Primary data is obtained through interviews and observation while secondary data is obtained through documentation.